Usaha Gambir Rakyat di Lima Puluh Kota, Sumatera Barat 1833-1930 - Selfi Mahat Putri (Lembaran Sejarah, 2013)
Existing studies on the economic history of plantations have hardly considered gambir, (or cat’s claw, Uncaria gambir roxb.), as a marketable commodity. In fact, during the colonial time in Indonesia gambir was one of the export commodities that formed the core of the people’s economy. This paper examines some aspects of the growth and socio-economic functions of the gambir plantations in the West Sumatra region of Lima Puluh Kota in the period from 1833 to 1930. It argues that the production and the marketing of gambir as an export commodity excelled other commodities in terms of quantity in the early period under study. However, the fact that gambir continued to be exported as a raw material made the decline of its popularity compared to other commodities such as coffee and pepper.